Persoalan Kerawanan Pangan pada Masyarakat Miskin di Wilayah Perbatasan Entikong (Indonesia-Malaysia) Kalimantan Barat - Niko, Nikodemus; Atem, Atem (Universitas Muhammadiyah Semarang, 2020)
The issue of food security has long since developed, both among the international community and national communities in Indonesia. In some processes and forms of national food security, the Government encourages the development of local food-based communities. In the community in Entikong, the implementation of this program is still not seen as an exact condition in thehandling of food issues at the borders of the country. Border society is still food dependence on Malaysia. The idea of making Indonesian society self-sufficiency in food has long been a crucial sector of individual attention to the Government. Many empowerment programs are found in the community that is the meeting point for overcoming food insecurity, so it is a new way forthe border community out of the inferior zone. The method used is a descriptive exploratory where the source of the data comes from the primary data referring directly to the situation of the border society of Entikong, while the secondary data of the desk review results related to the potential and state of the food community In the Entikong border area. The findings in this paper are that Entikong has economic potential, strategic location, and formal access support that has been qualified to advance. However, this situation is uneven; there are still areas of isolated villages and limited access. Then, the construction of international Terminal Goods (TBI) on the border became a breath of fresh air for the Entikong to multiply and make Entikong as the center of activity and economic development, including the food Center for the region Indonesia and as part of Malaysia.